Peningkatan Motivasi Belajar Siswa dalam Pembelajaran IPS dengan Menggunakan Media Gambar pada Kelas III Di SDN Larangan Badung 1 Palengaan Pamekasan - Sunu, Sunu (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this research is to enhance student motivation in social studies learning by using visual media in the third grade at SDN Larangan Badung 1 Palengaan Pamekasan. This research is a Classroom Action Research (CAR) conducted in two cycles. The subjects of this study are the third-grade students of SDN Larangan Badung 1. Each cycle consists of 4 stages: planning, implementation, observation, and reflection. Data collection in this study uses observation, interviews, and documentation. The data obtained are analyzed qualitatively and quantitatively in a descriptive manner. The results of the research in cycle 1 during the first meeting showed an average percentage of student motivation to learn categorized as very low at 37.5%, and in the second meeting, the average percentage of student motivation to learn reached 57.5%. In cycle II, during the first meeting, the average student motivation to learn experienced an increase, although it still did not reach the success indicator of 75%, which falls under the sufficient category. In the second meeting, the average percentage of student motivation to learn increased, reaching 85% in the very good category